Perception of Pak-China Relations in International Press: Comparative Analysis - Muhammad Imran; Dr. Zubair Shafiq Jatoi (Journal of Peace, Development and Communication, 2021)
This research has been conducted to examine and explain the coverage and slant of China-Pakistan bilateral relationship in the editorial pages (including Editorials and columns) of four noted newspapers in the world, The New York Times from the United States, the Times of India from India, Global Times from China and Daily Dawn From Pakistan have been selected for this research. Topic contains most of the important developments, such as the "China-Pakistan Economic Corridor" and "Military and Strategic Cooperation". The study includes a presentation of Pakistani-Chinese relations, as well as their important dimensions during the time period of January 2015 to December 2019. Quantitative and qualitative content analysis methods were applied to examine the selected categories of Sino-Pak relations. Coverage is analyzed in three dimensions, including positive, negative and neutral, in order to develop balanced criticism, taking into account both the frequency and the severity of the reporting. The theoretical basis is based on hypothesizes taken from the theory of framing. All target and identified categories were systematically tabulated and discussed. Study concluded that the Pakistani press gave more coverage to the stories related to Sino-Pak relations than other selected newspapers. Moreover, the Pakistani and Chinese press portray positive, while the Indian and American press cover it negatively. The study contributes to understand the perception of international press about regional affairs. Key Words: Portrayal, Media Framing, Pakistan-China Relations, Content Analysis, The New York Times, Times of India, Global Times, Daily Dawn.